Impact of a general practice based group parenting programme: quantitative and qualitative results from a controlled trial at 12 months. Issue 6 (21st May 2004) - Stewart-Brown, S; Patterson, J; Mockford, C; Barlow, J; Klimes, I; Pyper, C
Abstract : Aims: To test the effectiveness at one year of the Webster Stratton Parents and Children Series group parenting programme in a population sample of parents. Methods: In a multicentre block randomised controlled trial, parents of children aged 2–8 years in 116 families who scored in the upper 50% on a validated behaviour inventory, took part in Webster-Stratton's 10 week parenting programme led by trained and supervised health visitors. The following outcome measures were used: Eyberg Child Behaviour Inventory, Goodman Strengths and Difficulties Questionnaire, General Health Questionnaire, Parenting Stress Index, Rosenberg Self Esteem Scale. Results: The intervention significantly reduced child behaviour problems and improved mental health at immediate and 6 month follow ups. One year differences between control and intervention groups were not significant. Qualitative results suggest that these findings might be attributable in part to either Hawthorne effects or contamination of control group. At interview parents described ways in which the programme had improved their mental health. They reported gains in confidence and feeling less stressed. Some also reported beneficial changes in their own and their children's behaviour and improved relationships with their children. Some spoke of a need for further sessions to support the behaviour changes they had managed to make, and some the desire for attendance by both parents. Conclusions: Parenting programmes have the potential to promote mental health and reduce social inequalities, but further work is needed to improve long term effectiveness.